Mutual Funds - Lisa Leslie; Michael S. Gutter (EDIS)
Mutual funds are open-end investment companies that use a pool of many investors’ money to buy shares of different investments. They can be an effective way for the average investor to build a diverse portfolio. Although these funds come with fees, taxes, and, in the case of load funds, commissions, an investor still has the potential to achieve positive returns and beat inflation. This 4-page fact sheet was written by Lisa Leslie and Michael S. Gutter and published by the UF Department of Family Youth and Community Sciences, February 2013.